2007
DOI: 10.1016/j.neuropsychologia.2007.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Lesion correlates of conversational speech production deficits

Abstract: We assess brain areas involved in speech production using a recently developed lesion-symptom mapping method (voxel-based lesion-symptom mapping, VLSM) with 50 aphasic patients with left-hemisphere lesions. Conversational speech was collected through a standardized biographical interview, and used to determine mean length of utterance in morphemes (MLU), type token ratio (TTR) and overall tokens spoken for each patient. These metrics are used as indicators of grammatical complexity, semantic variation, and amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 41 publications
5
94
0
1
Order By: Relevance
“…8) in line with previous reports assessing verbal fluency but also conversational speech (Borovsky et al, 2007).…”
Section: Lesion Correlates Of Additional Specific Testssupporting
confidence: 90%
See 1 more Smart Citation
“…8) in line with previous reports assessing verbal fluency but also conversational speech (Borovsky et al, 2007).…”
Section: Lesion Correlates Of Additional Specific Testssupporting
confidence: 90%
“…Studies on verbal fluency (Bates et al, 2003;Baldo et al, 2006), sentence comprehension of varying syntactic complexity Magnusdottir et al, 2012), speech production (Dronkers and Ogar, 2004;Borovsky et al, 2007), noun versus verb naming (Piras and Marangolo, 2007), verbal and nonverbal semantics (Acres et al, 2009;Schwartz et al, 2009;Walker et al, 2011), picture naming (Rudrauf et al, 2008;Cloutman et al, 2009;Parkinson et al, 2009;Piras and Marangolo, 2010) word and number reading (Piras and Marangolo, 2009), and speech repetition (Fridriksson et al, 2010) provide an increasingly detailed map of areas mandatory for specific linguistic subfunctions. Additionally the overlap between linguistic and more general cognitive processing has been targeted (Leff et al, 2009) and subcortical connections constituting the network have been investigated (Turken and Dronkers, 2011;Kummerer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the anterior insula is often associated with the processing of disgust or other emotionally valent stimuli (Schienle et al, 2002), it has also been shown to have very strong connections with the inferior frontal gyri (Jabbi & Keysers, 2008) and to contribute to speech production (Ackermann & Riecker, 2004;Borovsky, Saygin, Bates, & Dronkers, 2007). For instance, it has been suggested that the insulae play a role in the control of vocal tract musculature (Ackermann & Riecker, 2004Ackermann & Riecker, 2010Riecker, Ackermann, Wildgruber, Dogil, & Grodd, 2000), and neuropsychological evidence associates lesions to the anterior insula with speech production deficits (Dronkers, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with articulatory dysfunction in the absence of a muscular problem (i.e., dysarthria), had lesions in the left superior tip of the precentral gyrus of the insula (Dronkers, 1996). Other studies with patients with progressive apraxia (Nestor el al., 2003), reduced fluency (Bates et al, 2003;Borovsky et al, 2007), or impairments with rapidly changing articulatory movements (Baldo et al, 2011) were also reported to have left anterior insular damage. Neuroimaging studies with healthy studies also suggested that the left precentral gyrus of the insula is involved in articulatory coordination (Murphy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%